Antimicrobial susceptibility and molecular profiles of acinetobacter baumannii in Makkah hospitals, and the potential use of bacteriophage as a treatment option - Raees, Fahad (2022)
Acinetobacter baumannii is an opportunistic Gram-negative pathogen that frequently causes infections especially in intensive care settings worldwide including Saudi Arabia. This organism is known to acquire resistant to almost all clinically available antimicrobial agents. To understand the magnitude of A. baumannii acquisition in local settings, 895 isolates were collected from King Abdullah Medical City Makkah, Al Noor Hospital and Al Zahir Hospital of Makkah from 2013-2019. Vitek2® system was used for identification of the organism and antimicrobial susceptibility test. Thirty MDR A. baumannii isolates from King Abdullah Medical City Makkah and seven from Al Noor Hospital were selected for whole genome sequencing. To study the role of bacteriophage, sewage water from King Abdullah Medical City Makkah and Al Noor Hospital were screened for clinical isolates A. baumannii lytic phenomenon. A few bacteriophage candidates were found, but the subsequent lytic tests were negative. This phenomenon was studied by reviewing the bacteriophage genomes integrated in the bacterial nucleic acids. In this study, 70-80% of A. baumannii isolated from Makkah hospitals were found to be resistant to commonly used antibiotics in intensive care units. There are increasing trends of resistance to agents that been reserved to treat carbapenem-resistant A. baumannii i.e. tigecycline and colistin. The sequence type (ST)-195 was the predominant sequence type, contributed to 48.6% of A. baumannii isolations in Makkah hospitals. There were three novel sequence types that associated with 18.9% of infections that need further characterization. Among the β-lactamase resistant mutations, this study found blaADC-25 and blaOXA-66 were the most common with 86.5% and 83.8% respectively, followed by blaOXA-23 and blaTEM-1D, both at 37.8%. This study also found 75.7% and 73.0% of the tested MDR A. baumannii isolated from Makkah hospitals acquired mph(E) and msr(E) macrolides resistant genes respectively. The aminoglycosides resistance was encoded mainly by aminoglycoside phosphor-transferase gene, aph(3′′)-Ib at 83.8% and aminoglycoside O-phosphotransferase aph(6)-Id at 70.3%. Besides, these MDR isolates were also acquired of sulphonamide resistant genes of sul1 (32.4%) and sul2 (18.9%). Part of the core of this project was to find the potential bacteriophage that has capability to infect and lyse A. baumannii cells. After extensive searching for bacteriophage from sewage water of two tertiary care hospitals in Makkah, several bacteriophage candidates were shortlisted, however these bacteriophages failed to perform lytic phenomenon consistently. Almost one-fourth of MDR A. baumannii were found to acquire intact bacteriophage genomes, indicated prophages condition. The whole genome sequence of two MDR A. baumannii isolates (AB417 and AB552) were studied before and after bacteriophage treatment indicated additional intact bacteriophage genomes were added in isolate AB552. Three genomes of non-Acinetobacter bacteriophages was found to be integrated in these MDR Acinetobacter series. In conclusion, this study found the resistant rate of A. baumannii were more than 80% in Makkah hospitals which may lead to treatment failure in clinical practice. Searching for a non-pharmacological approach by means of using bacteriophage therapy showed inconsistent outcomes. With few treatment options available, robust infection control strategies and antibiotic stewardship programs are critical for preventing the spread of these resistant strains. Further research is very critical to find alternative agents to treat MDR A. baumannii.